ANALISA KERUSAKAN PERKERASAN JALAN MENURUT METODE BINA MARGA DAN PCI ( PAVEMENT CONDITION INDEX ) SERTA ALTERNATIF PENANGANANNYA ( STUDI KASUS RUAS JALAN KOTA BANGUN – GUSIK ) - WAHYUDI, FIRMAN (KURVA S JURNAL MAHASISWA, 2018)
Kota Bangun-Gusik Road is a national road link between East Kalimantan and Central Kalimantan, so that it becomes a land transportation infrastructure that includes all parts of the road, including complementary buildings and equipment intended for traffic, which is above ground level, below ground level or water. The 30 km long Bangun-Gusik Kaltim City Road section suffered significant damage, both minor damage, moderate damage and severe damage to some of these roads. The purpose of this study was to determine the type and extent of damage to the road surface, and provide measures to repair road damage based on the level and type of damage that occurred. The stages of analysis in writing this thesis are by conducting an LHR survey, visual survey at the research location, determining the type and level of damage and measuring the dimensions of damage which includes the length, width and damage that occurs, calculating the area of damage, analyzing the surface damage conditions of the Build City Road - Gusik by calculating the PCI value and the overall Road Condition value using the Pavement Condition Index (PCI) method and the Bina Marga (1990) method. The results of the analysis based on the data obtained from the field survey indicate that the value of the road conditions or ratting given by Pavement Condition Index (PCI) is 59.91 for the overall average based on the ratting value of PCI between 56 to 70 in Good and value conditions given by Bina Marga amounting to 7.91 based on Bina Marga's priority value between 7 to 10, routine maintenance is carried out.